A Low Profile Wideband Log Periodic Microstrip Antenna Design for C-Band Applications - Yerlikaya, M.; Gültekin, S. S.; Uzer, D. (Advanced Electromagnetics, 2019)
In this study, a wideband low profile microstrip antenna design for C-band applications is presented. The proposed antenna consists of a monopol log periodic patch in the equilateral triangular dimensions with the microstrip line fed and a rectangular ground plane. The antenna has 9×19.8 mm2 overall size, thickness of 1.6 mm and 4.3 dielectric constant. According to the simulation results, the proposed antenna has a very wide bandwidth while operating in the frequency band of 4.25-7.95 GHz and 5 GHz resonance frequency. The proposed antenna was also prototyped on FR4 substrate with the 0.02 tangent loss and the measurement results were quite similar by the simulated results.